2016
DOI: 10.1177/1933719116630419
|View full text |Cite
|
Sign up to set email alerts
|

In Estimated Good Prognosis Patients Could Unexpected “Hyporesponse” to Controlled Ovarian Stimulation be Related to Genetic Polymorphisms of FSH Receptor?

Abstract: It has been reported that 10% to 15% of young normogonadotrophic women show suboptimal response to standard gonadotropin-releasing hormone-a long protocol. These patients require higher doses of exogenous follicle-stimulating hormone (FSH). This phenomenon could be associated with genetic characteristics. In this study, FSH receptor polymorphism was retrospectively evaluated in 42 normoresponder young women undergoing an in vitro fertilization/intracytoplasmic sperm injection cycle; patients were stratified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
1
44
0
3
Order By: Relevance
“…In a 2013 sizeable longitudinal study, we found that a common LH beta subunit variant was associated with increased FSH consumption during OS ( 29 ). In another study, we found that the prevalence of hypo-response was higher in G allele carriers of a common FSH receptor (FSHR) polymorphism (p.N680SA > G, rs6166) than in wild-type haplotypes ( 30 ). Furthermore, in vitro studies using human granulosa cells demonstrated that p.N680SA>G G homozygous showed higher resistance to FSH stimulation than p.N680SA>G A homozygous carriers at the FSH receptor level ( 31 , 32 ).…”
Section: Pathogenesis Of Hypo-responsementioning
confidence: 96%
“…In a 2013 sizeable longitudinal study, we found that a common LH beta subunit variant was associated with increased FSH consumption during OS ( 29 ). In another study, we found that the prevalence of hypo-response was higher in G allele carriers of a common FSH receptor (FSHR) polymorphism (p.N680SA > G, rs6166) than in wild-type haplotypes ( 30 ). Furthermore, in vitro studies using human granulosa cells demonstrated that p.N680SA>G G homozygous showed higher resistance to FSH stimulation than p.N680SA>G A homozygous carriers at the FSH receptor level ( 31 , 32 ).…”
Section: Pathogenesis Of Hypo-responsementioning
confidence: 96%
“…The presence of genetic mutations or single nucleotide polymorphisms of Gn and their receptors can influence ovarian sensitivity to Gn stimulation (17,18). Apart from genotypic traits, there is also evidence to suggest that environmental contaminants and oxidative stress are involved in the hyporesponse pathogenesis (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian response in IVF is clearly dependent on the genotype of the FSH receptor (30) . Different variants in receptor genotype have been related to different basal FSH levels and to different numbers of FSH ampoules needed to achieve adequate ovarian response in IVF (31) .…”
Section: Discussionmentioning
confidence: 99%